The Development of Structural Design and the Selection of Design Parameters of Aerodynamic Systems for De-orbiting Upper-stage Rocket Launcher - Alpatov, A.P.; Palii, O.S.; Skorik, О.D. (Science and Innovation, 2024)
The aerodynamic systems for upper-stage rocket launcher de-orbit have been analyzed. The feasibility and possibility of creating aerodynamic inflatable deorbit systems have been established. A mathematical model of upper-stage rocket launcher orbital motion has been developed. The aerodynamic deorbit system parameters for various configurations neglecting effects of space factors have been calculated. The effect of space factors on the aerodynamic deorbit system has been estimated. The effect of atomic oxygen and cosmic vacuum (sublimation) has been showed to lead to a decrease in shell thickness, while space debris causes an increase in consumption of working substance to inflate shell. The structural design has been selected and aerodynamic deorbit system parameters have been calculated with effect of space factors taken into account.